PERLINDUNGAN HUKUM BAGI PENCIPTA MUSIK DAN LAGU ATAS TINDAKAN ARANSEMEN ULANG TANPA IZIN OLEH PENGGUNA APLIKASI TIKTOK - Algiffari, Rafid; Arifudin, Ery (JIPRO: Journal of Intellectual Property, 2023)
Law No. 28 of 2014 regulates copyright but there are still many copyright violations in the TikTok application, therefore there is still a need for copyright protection. Copyright protection is needed to prevent copyright disputes. This study examines the legal protection for music and song creators for unauthorized re-arrangements by TikTok application users and the responsibility of the perpetrators of unauthorized re-arrangements of the owner's copyright. This research is a normative research using the approach of legislation, cases, and concepts. The data analysis used is examining library materials such as books, journals, laws, scientific articles related to these legal issues. This study shows that preventive protection of creators' copyrights is less than optimal, because the legal protection and supervision provided by the government are not supported by the TikTok application, which is less assertive in regulating copyright violations in the form of musical arrangements, even the TikTok application tends to let go of copyright violations in the form of re-arranging music. Therefore, the responsibility for arranging without permission is not carried out optimally.